Safety and pharmacodynamics of intranasal GSK2245035, a TLR7 agonist for allergic rhinitis: A randomized trial. Issue 9 (11th August 2017) - Ellis, A. K.; Tsitoura, D. C.; Quint, D.; Powley, W.; Lee, L. A.
Summary: Background: Toll‐like receptor 7 (TLR7) stimulation in the airways may reduce responses to aeroallergens by induction of type 1 interferons (IFNs). GSK2245035 is a novel selective TLR7 agonist in pharmaceutical development. Objective: Assessment of safety, pharmacodynamics and nasal allergic reactivity following repeated weekly intranasal (i.n.) GSK2245035. Methods: This randomized, double‐blind, placebo‐controlled study (TL7116958) was conducted over two pollen seasons (2013‐2014) and follow‐up study (204509) conducted 1 year later. Participants with allergic rhinitis (n=42) were randomized to receive eight weekly doses of i.n. GSK2245035 (20 ng [2014 Cohort; n=14] or 80 ng [2013 Cohort; n=14]) or placebo (n=14). Adverse events (AEs) including cytokine release syndrome AEs (CytoRS‐AEs) and nasal symptoms were assessed. Nasal and serum IFN‐inducible protein 10 (IP‐10) were measured after doses 1 and 8, then 1 (follow‐up visit [FUV] 1) and 3 (FUV2) weeks after final dose. Nasal allergen challenges (NACs) and allergic biomarker assessment (nasal, serum) were conducted at baseline, FUV1, FUV2 and at a FUV 1 year after final dose (FUV3; 2014 Cohort only). A Bayesian framework enabled probability statements for mean effect sizes. Results: GSK2245035 induced CytoRS‐AEs (most commonly headache, median duration <1 day) in 93% of participants at 80 ng, while AE incidence at 20 ng was similar to placebo. There was no evidence of nasal inflammation. Dose‐related increases in nasal and serum IP‐10 were observed 24 hours after doses 1 and 8 (>95% certainty). Both doses showed a trend in reducing total nasal symptom score 15 minutes post‐NAC at FUV1 and FUV2, but there was no reduction evident at FUV3. Nasal levels of selected allergic biomarkers demonstrated trends for reductions at FUV1, FUV2 and FUV3. Conclusions and clinical relevance: Weekly i.n. GSK2245035 20 ng was well tolerated and reduced allergic reactivity to nasal challenge for 3 weeks post‐treatment.